2020
DOI: 10.1038/s41593-020-00757-6
|View full text |Cite
|
Sign up to set email alerts
|

Microglia facilitate repair of demyelinated lesions via post-squalene sterol synthesis

Abstract: The repair of inflamed, demyelinated lesions as in multiple sclerosis necessitates the clearance of cholesterol-rich myelin debris by microglia/macrophages and the switch from a pro-inflammatory to an anti-inflammatory lesion environment. Subsequently, oligodendrocytes increase cholesterol levels as a prerequisite for synthesizing new myelin membranes. We hypothesized that lesion resolution is regulated by the fate of cholesterol from damaged myelin combined with oligodendroglial sterol synthesis. By integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
191
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(213 citation statements)
references
References 66 publications
10
191
1
1
Order By: Relevance
“…Desmosterol, in turn, signals via the liver X receptor (LXR) to induce lipid efflux and secretion of reparative factors to support remyelination. Indeed, inducing sterol synthesis promoted quicker remyelination in vivo (156). Conceptually, each tissue features unique accessory and primary cell types, as highlighted in the above studies, that function collectively to perform the required functions of that tissue.…”
Section: Metabolism Of Homeostatic and Pro-resolving Tissue-resident Macrophagesmentioning
confidence: 96%
See 1 more Smart Citation
“…Desmosterol, in turn, signals via the liver X receptor (LXR) to induce lipid efflux and secretion of reparative factors to support remyelination. Indeed, inducing sterol synthesis promoted quicker remyelination in vivo (156). Conceptually, each tissue features unique accessory and primary cell types, as highlighted in the above studies, that function collectively to perform the required functions of that tissue.…”
Section: Metabolism Of Homeostatic and Pro-resolving Tissue-resident Macrophagesmentioning
confidence: 96%
“…This circuit was tunable, allowing for both improved and impaired muscle regeneration across multiple in vivo models (155). In the second study, Nave, Saher, and colleagues report that microgliamediated CNS repair depends on the synthesis of desmosterol (instead of the sterol synthesis end-product cholesterol) from the engulfed myelin (156). Desmosterol, in turn, signals via the liver X receptor (LXR) to induce lipid efflux and secretion of reparative factors to support remyelination.…”
Section: Metabolism Of Homeostatic and Pro-resolving Tissue-resident Macrophagesmentioning
confidence: 99%
“…Very little is known about metabolic requirements of CNS remyelination (Figure 3). A recent paper suggested that microglial synthesis of desmosterol, a cholesterol precursor, was required to support remyelination in mice subjected to cuprizone intoxication by stimulating lipid recycling for myelin synthesis [99]. This paper also suggested that OPC synthesis of cholesterol was not crucial for remyelination.…”
Section: Energetic Support Of Remyelination?mentioning
confidence: 99%
“…Remyelinating adult OPCs/new oligodendrocytes have been reported to rely on glycogen-derived lactate released by astrocytes in a cuprizone model [98]. In addition, synthesis of desmosterol by microglia has been shown to stimulate lipid recycling after demyelination and drive remyelination [99].…”
Section: Ketone Bodies As An Important Energy Fuel During Developmental Myelinationmentioning
confidence: 99%
“…One recent study found that a Western diet impairs recovery from demyelinating injuries, by inhibiting microglial phagocytosis and clearance of lipid debris ( 25 ). Another study found that in the setting of demyelination, microglia synthesize desmosterol, the immediate cholesterol precursor and liver X receptor (LXR) agonist, and that microglial sterol synthesis is essential for efficient remyelination ( 26 ). As oligodendrocytes were thought to be the primary synthesizers of sterols in the brain, and require sterols for myelination, this indicates a new role for intercellular trafficking of sterols.…”
Section: Lipid Metabolism In the Brainmentioning
confidence: 99%